Vibration-based nondestructive testing as a practical tool for rapid concrete quality control. (1st February 2016) - Aguilar, Rafael; Ramírez, Eduardo; Haach, Vladimir G.; Pando, Miguel A.
Highlights: Study related to vibration-based non-destructive testing for QC/QA of concrete. A correlation of dynamic E-modulus and compressive strength was identified. NDT were useful to track the evolution of static and dynamic E-modulus in time. A relationship of expected E-moduli from measurements at earlier ages is proposed. Proposed predictive correlations include compressive strength to dynamic E-modulus. Abstract: This paper involves a practical approach to perform quality-control/quality-assessment of concrete using vibration-based NDT. The first component is the analysis of compressive strength and dynamic E-modulus of concrete samples from various construction projects. The second component involves continuous measurements of E-Moduli as a function of curing time in laboratory-controlled specimens. The experimental program allowed proposing a correlation to predict the expected static and dynamic E-modulus at 28 days from their measurement at any instant of the curing process. A similar relationship is proposed to predict compressive strength at 28 days based on the dynamic E-modulus measured at earlier ages.